Perkembangan Kognitif Anak Usia Dini Usia 5-6 Tahun di Paud KB Ananda - Adiani Hulu; Erniman Amazihono; Melva Irmawati Tamba; Windhy Rohana Panggabean; Nissa Meilani Sinurat; Senila Zalukhu (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This paper discusses the cognitive development of 5-6 year old children in PAUD KB Ananda. Early childhood cognitive abilities in PAUD KB Ananda are described in this study. It includes aspects of cognitive development such as creativity, problem-solving, memory, and thinking skills. This research was conducted through case studies and a qualitative descriptive approach. Data was collected through observation, interviews with teachers and parents. The results of the study showed that most children in PAUD KB Ananda showed good cognitive development according to their age, although there were individual differences in development levels. Certain children are highly creative and critical, but some require further stimulation for some cognitive aspects.